Co-metabolic substrates enhanced biological nitrogen removal from cellulosic ethanol biorefinery wastewater using aerobic granular sludges. Issue 3 (28th January 2020) - Wang, He; Li, Xue; Gong, Zhiyuan; Wang, Xiaolong; Liang, Hong; Gao, Dawen
ABSTRACT: The effect of different co-metabolic substrates (glucose, acetic acid and ethanol) on aerobic granular sludge treating cellulose ethanol wastewater was investigated using sequencing batch reactors. The efficiencies of the three substrates in removing chemical oxygen demand were respectively 18.87%, 28.88% and 27.99%, all of which were remarkably higher than without co-metabolic substrates, indicating that co-metabolic substrates can promote the degradation of the refractory substances. With acetic acid as the co-metabolic substrate, the removal amount of ammonium nitrogen and nitrate nitrogen was greater than glucose and ethanol used. The nitrogen removals by the three co-metabolic substrates were 53.18%, 72.15%, 69.36%, respectively, which were 1.4, 1.8, and 1.6 times the removal without co-metabolic substrates. Fluorescence in situ hybridization results showed that the proportion of ammonium-oxidizing bacteria in the granular sludge was greater than that of nitrite-oxidizing bacteria after adding co-metabolic substrates, and the order was acetic acid > ethanol > glucose. GRAPHICAL ABSTRACT: